The impact of Innovation in offering the banking services in achieving competitive advantage for banks ( An applied study in the Iraqi private Banks ) - محمد, ايمان عبد الرضا (Journal of Economics and Administrative Sciences, 2013)
This research aims at recognizing the concept of Innovation in offering the banking services as well as the concept and dimensions of competitive advantage . And to identify and analyze the relationship ( correlation and impact ) between the concept of Innovation in  offering the banking services and the dimensions of the competitive advantage under discussion . The research includes all Iraqi private banks in Baghdad city only of the (20) banks . The researcher adopted , in this study , a random sample of the distribution of the questionnaire to members of the research sample are managers , customers and employees in these banks , and were distributed ( 115 ) form  questionnaire , ( 97 ) form ware restored which are suitable for analysis . The research found a group of important results correlated and impact statistically significant between Innovation in providing banking services and dimensions of competitive advantage in the researched banks . The research has included a series of recommendations including : managers and workers should be concerned in the researched banks about the relationship (correlation and impact ) between the concept of Innovation in  offering the banking services and the dimensions of competitive advantage , and departments should be concerned in the researched banks with dimensions of competitive advantage and work to achieve them efficiently in order to achieve superiority over its competitors in the market competition